Peningkatan Kompetensi Guru dalam Penulisan Instrumen Tes Literasi Sains Pada Guru Sekolah Dasar di SD Negeri Bulustalan - Sri Wardani; Sri Haryani; Sarwi Sarwi; Agung Tri Prasetya; Margaretha Novita Rupa Lobemato; Dwi Septiaseh (Universitas Negeri Makassar, 2022)
The preparation of scientific literacy tests is very important knowledge for teachers in 21st-century learning. Therefore, teachers must have knowledge about the preparation of scientific literacy tests for students. This service research aims to increase knowledge about ways to arrange a scientific literacy test through the teachers of the Bulustalan State Elementary School. Participation in training activities through this service are all teachers at the Bulustalan State Elementary School. The method used in this service research is to use the lecture, practice, and assignment methods. This service activity has a good impact, namely providing insight to teachers about literacy test instruments to face the 21st century and increasing teacher competence related to skills in preparing scientific literacy test instruments that can be integrated into the form of multiple-choice tests and essay tests.